Lack of association between CGRP-related gene polymorphisms and medication overuse headache in migraine patients. Issue 1 (2015) - Ishii, Masakazu; Katoh, Hirotaka; Kurihara, Tatsuya; Saguchi, Ken-ichi; Shimizu, Shunichi; Kawamura, Mitsuru
No abstract available